2015
DOI: 10.18632/oncotarget.5361
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 receptor α2 is a negative prognostic factor in human lung cancer and stimulates lung cancer growth in mice

Abstract: IL-13 receptor subunit alpha-2 (IL13Rα2) is associated with poor prognosis in some cancers. However, the role of IL13Rα2 in lung cancer remains unknown. We showed that IL13Rα2 overexpression was associated with late stages of disease progression and shorter disease-free survival (DFS) as well as overall survival (OS) in resected lung cancer patients. IL13Rα2 promoted the migration, invasion and anoikis resistance of lung cancer cells in vitro. Silencing of IL13Rα2 in lung cancer cells decreased invasion in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…Our team has discovered that IRS-1 activated the PI3K-Akt signaling pathway to enhance the proliferation of the primary rat osteoblasts (Ma et al, 2015). Although we found that the increased TAZ expression induced by IGF1 is mostly mediated by the MEK-ERK pathway rather than the PI3K-Akt signaling pathway in our previous research (Xue et al, 2013), Xie et al (2015) reported that inhibition of the PI3K-Akt pathway could attenuate the activation of TAZ expression in lung cancer cells. Our results revealed that the PI3K-Akt pathway inhibitor, LY294002, offsets the IRS-1 induced upregulation of TAZ expression, which points to a link between the IRS-1/PI3K-Akt signaling pathway and the TAZ/RUNX2 transcriptional complex during osteoblast maturation.…”
Section: Discussioncontrasting
confidence: 66%
“…Our team has discovered that IRS-1 activated the PI3K-Akt signaling pathway to enhance the proliferation of the primary rat osteoblasts (Ma et al, 2015). Although we found that the increased TAZ expression induced by IGF1 is mostly mediated by the MEK-ERK pathway rather than the PI3K-Akt signaling pathway in our previous research (Xue et al, 2013), Xie et al (2015) reported that inhibition of the PI3K-Akt pathway could attenuate the activation of TAZ expression in lung cancer cells. Our results revealed that the PI3K-Akt pathway inhibitor, LY294002, offsets the IRS-1 induced upregulation of TAZ expression, which points to a link between the IRS-1/PI3K-Akt signaling pathway and the TAZ/RUNX2 transcriptional complex during osteoblast maturation.…”
Section: Discussioncontrasting
confidence: 66%
“…With respect to IL-13, a recent study observed the highest expression level of IL-13 in LC in the SQC subtype, followed by the ADC subtype [139]. Moreover, a clear association between IL-13 receptor subunit alpha-2 overexpression and poor survival in resected NSCLC patients has been shown [140]. There are other profibrotic cytokines besides IL-13 that are also associated with IPF.…”
Section: Principal Fibrogenic Molecules and Signal Transduction Pamentioning
confidence: 99%
“…In LC, the CCL2/CCR2 (chemokine receptor type 2) axis is also important in several aspects of tumorigenesis. One of its most important roles is the generation of new vascular structures that allow tumour growth [140]. However, there is evidence of an association between CCL2 in cancer cells and better survival in NSCLC patients [143].…”
Section: Principal Fibrogenic Molecules and Signal Transduction Pamentioning
confidence: 99%
“…Studies showed that IL13Rα2 positively regulates HCC through activation of the TGF-β1 promoter, increasing TGF-β1 production and fibrosis progression [11,15]. Others suggested that it might mediate its effect via activating the Yes-associated protein (YAP) and/or transcriptional coactivator with PDZ-binding motif (TAZ) in hippo signaling [15,16]. Interestingly, the hippo pathway transcriptional activator TAZ was recently correlated in fibrosis progression in NASH [17].…”
Section: Introductionmentioning
confidence: 99%